Effect of Different Drip Irrigation Level on Yield Attributes of Coloured Capsicum Hybirds (Capsicum annuum var. grossum L.) Under Shade net - A. SRINIVAS, B. KIRUTHIGA, K. AVIL KUMAR, K. SREENIVASA KUMAR and (The Journal of Research, PJTSAU, 2020)
Capsicum is also known as bell pepper orsweet pepper or shimla mirchi which is a cool seasontropical crop, belongs to the family Solanaceae, andis native of South and Central America. Fruits of Shimlamirchi are large (usually bell shaped; hence calledbell pepper) and non-pungent (hence also called sweetpepper). The term Shimla mirchi originated becauseprobably it was first cultivated in Shimla region(temperate climate), which was suitable for itscultivation. It attained a status of high value crop inIndia in recent years, occupying an area of 46 thousandhectares, producing 327 thousand metric tons.